Stratified care versus usual care for management of patients presenting with sciatica in primary care (SCOPiC): a randomised controlled trial. (July 2020) - Konstantinou, Kika; Lewis, Martyn; Dunn, Kate M; Ogollah, Reuben; Artus, Majid; Hill, Jonathan C; Hughes, Gemma; Robinson, Michelle; Saunders, Benjamin; Bartlam, Bernadette; Kigozi, Jesse; Jowett, Sue; et al.
Summary: Background: Sciatica has a substantial impact on individuals and society. Stratified care has been shown to lead to better outcomes among patients with non-specific low back pain, but it has not been tested for sciatica. We aimed to investigate the clinical and cost-effectiveness of stratified care versus non-stratified usual care for patients presenting with sciatica in primary care. Methods: We did a two-parallel arm, pragmatic, randomised controlled trial across three centres in the UK (North Staffordshire, North Shropshire/Wales, and Cheshire). Eligible patients were aged 18 years or older, had a clinical diagnosis of sciatica, access to a mobile phone or landline number, were not pregnant, were not currently receiving treatment for the same problem, and had no previous spinal surgery. Patients were recruited from general practices and randomly assigned (1:1) by a remote web-based service to stratified care or usual care, stratified by centre and stratification group allocation. In the stratified care arm, a combination of prognostic and clinical criteria associated with referral to spinal specialist services were used to allocate patients to one of three groups for matched care pathways. Group 1 was offered brief advice and support in up to two physiotherapy sessions; group 2 was offered up to six physiotherapy sessions; and group 3 was fast-tracked to MRI and spinal specialist assessment within 4 weeks of randomisation. The primary outcome was self-reported time to first resolution of sciatica symptoms, defined as "completely recovered" or "much better" on a 6-point ordinal scale, collected via text messages or telephone calls. Analyses were by intention to treat. Health-care costs and cost-effectiveness were also assessed. This trial is registered on the ISRCTN registry, ISRCTN75449581. Findings: Between May 28, 2015, and July 18, 2017, 476 patients from 42 general practices around three UK centres were randomly assigned to stratified care or usual care (238 in each arm). For the primary outcome, the overall response rate was 89% (9467 of 10 601 text messages sent; 4688 [88%] of 5310 in the stratified care arm and 4779 [90%] of 5291 in the usual care arm). Median time to symptom resolution was 10 weeks (95% CI 6·4–13·6) in the stratified care arm and 12 weeks (9·4–14·6) in the usual care arm, with the survival analysis showing no significant difference between the arms (hazard ratio 1·14 [95% CI 0·89–1·46]). Stratified care was not cost-effective compared to usual care. Interpretation: The stratified care model for patients with sciatica consulting in primary care was not better than usual care for either clinical or health economic outcomes. These results do not support a transition to this stratified care model for patients with sciatica. Funding: National Institute for Health Research.